PERANAN OPINION LEADER DALAM MENYAMPAIKAN PESAN TENTANG PEMBANGUNAN DESA DI DESA LANTUNG KECAMATAN WORI KABUPATEN MINAHASA UTARA - Rondonuwu, Sintje (JURNAL ADMINISTRASI PUBLIK, 2017)
Opinion Leaders is people who has capability to deliver message and also has experience andknowledge about information that can change the the other people mindset or behavior.The characteristic of the opinion leader is usually the first people who takes an initiative tocommunicate and contact the community to spread the information. The community often meetthe opinion leader in order to seek for information, that is why the opinion leader can be calledas an source of information. The opinion leader and the society or community shared the sameinterest in order to implement the village development. The success of the village developmentcan be occurred if the opinion leader takes a role in the village development process.Keywords: Role of Opinion Leader, Village Development